Structural Characterization of Lignin and Its Degradation Products with Spectroscopic Methods - Lu, Yao; Lu, Yong-Chao; Hu, Hong-Qin; Xie, Feng-Jin; Wei, Xian-Yong; Fan, Xing (Journal of Spectroscopy, 2017)
Lignin is highly branched phenolic polymer and accounts 15–30% by weight of lignocellulosic biomass (LCBM). The acceptable molecular structure of lignin is composed with three main constituents linked by different linkages. However, the structure of lignin varies significantly according to the type of LCBM, and the composition of lignin strongly depends on the degradation process. Thus, the elucidation of structural features of lignin is important for the utilization of lignin in high efficient ways. Up to date, degradation of lignin with destructive methods is the main path for the analysis of molecular structure of lignin. Spectroscopic techniques can provide qualitative and quantitative information on functional groups and linkages of constituents in lignin as well as the degradation products. In this review, recent progresses on lignin degradation were presented and compared. Various spectroscopic methods, such as ultraviolet spectroscopy, Fourier-transformed infrared spectroscopy, Raman spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy, for the characterization of structural and compositional features of lignin were summarized. Various NMR techniques, such as 1H, 13C, 19F, and 31P, as well as 2D NMR, were highlighted for the comprehensive investigation of lignin structure. Quantitative 13C NMR and various 2D NMR techniques provide both qualitative and quantitative results on the detailed lignin structure and composition produced from various processes which proved to be ideal methods in practice.